Morphological bases for intestinal paracellular absorption in bats and rodents - Brun, Antonio; Fernandez Marinone, Guido; Price, Edwin R.; Nell, Lucas A.; Simoes, Beatriz M. V. [UNESP]; Castellar, Alexandre [UNESP]; Gontero-Fourcade, Manuel; Cruz-Neto, Ariovaldo P. [UNESP]; Karasov, William H.; Caviedes-Vidal, Enrique (Wiley-Blackwell, 2019)
Flying mammals present unique intestinal adaptations, such as lower intestinal surface area than nonflying mammals, and they compensate for this with higher paracellular absorption of glucose. There is no consensus about the mechanistic bases for this physiological phenomenon. The surface area of the small intestine is a key determinant of the absorptive capacity by both the transcellular and the paracellular pathways; thus, information about intestinal surface area and micro-anatomical structure can help explain differences among species in absorptive capacity. In order to elucidate a possible mechanism for the high paracellular nutrient absorption in bats, we performed a comparative analysis of intestinal villi architecture and enterocyte size and number in microchiropterans and rodents. We collected data from intestines of six bat species and five rodent species using hematoxylin and eosin staining and histological measurements. For the analysis we added measurements from published studies employing similar methodology, making in total a comparison of nine species each of rodents and bats. Bats presented shorter intestines than rodents. After correction for body size differences, bats had similar to 41% less nominal surface area (NSA) than rodents. Villous enhancement of surface area (SEF) was similar to 64% greater in bats than in rodents, mainly because of longer villi and a greater density of villi in bat intestines. Both taxa exhibited similar enterocyte diameter. Bats exceeded rodents by similar to 103% in enterocyte density per cm(2) NSA, but they do not significantly differ in total number of enterocytes per whole animal. In addition, there is a correlation between SEF and clearance per cm(2) NSA of L-arabinose, a nonactively transported paracellular probe. We infer that an increased enterocyte density per cm(2) NSA corresponds to increased density of tight junctions per cm(2) NSA, which provides a partial mechanistic explanation for understanding the high paracellular absorption observed in bats compared to nonflying mammals.
Keywords: bats; enterocytes; nutrient absorption; rodents; small intestine surface area